Antecedents dan Consequences dari Feedback-Seeking Orientation di Costa Crociere - Trias Septyoari Putranto (Bina Nusantara University, 2012)
Cruise ship, as a home away from home place, which has a perisable product with the complex activity from their employees, certainly should have a potential character to keep sustainable in the service industry. To keep it sustainable, the management should have a good relationship with their employees and customers. In this research, a good relationship with the employee can be created by a good motivation, leadership, and it has an effect with the feedback. This condition can be seen by the employees’ job satisfaction. The management can drive a conductive working condition to help generate a good service climate. The research was undertaken in a cruise ship service industry in Italy. The purpose of this study was to evaluate the effect of employees’ motivation and leadership of feedback-seeking orientation and their job satisfaction. Sample was collected from 100 respondents, the employees’, with simple random sampling method, questionnaire, and an interview with the management. The collected data was analyzed with path analysis which using the statistic program LISREL 8.7 for Windows, and the questionnaire was adopted from Paswan (2005) and Chou (2002). The findings suggest that motivation and leadership have a significant effect on feedback-seeking orientation. Besides, feedbackseeking orientation also has a significant effect on job satisfaction.